Re-growth and Nutritional Potentials of Eleusine indica (L.) Gaertn. (Goose Grass) - Regmi, P.R.; Devkota, N.R.; Timsina, J. (Journal of the Institute of Agriculture and Animal Science, 2004)
Indigenous forage species, such as Eleusine indica could be an alternative to solve the problem of green roughage scarcity in Nepal. A study with E. indica was conducted to determine the re-growth and feeding value in Chitwan, Nepal during the dry season in 2002/2003. A field trial was carried out in a split plot design with nitrogen fertilizer rates (0, 50, and 100 kg N ha-1) and cutting heights (2, 4, 6 cm above the ground) as the main plot and sub-plot treatments, respectively. Proximate constituents of the harvested samples were analyzed and a consecutive digestibility trial was carried out with one-year-old local female goats to determine the feeding value. Increased number of tillers per plant and higher re-growth was obtained with 100 kg N ha-1 (P<0.05). However, cutting height had no significant effect (P>0.05) on forage re-growth. The cumulative forage re-growth of four harvests during dry season (Jan 2003 – May 2003) was about 11 t ha-1 with 100 kg N ha-1 and 2 cm cutting height. The dry matter (DM) and crude protein (CP) content of E. indica was 35.8% and 12.4%, respectively. The digestibility coefficient of the forage for DM, CP, crude fibre (CF) and ether extract (EE) was 53.5, 66.6, 69.6 and 53.7, respectively. The forage was found to be fairly palatable and had no adverse effect when fed to the goats. The findings of the study indicated that there is a potential for growing E. indica to overcome the problem of green roughage scarcity especially during the season in Nepal. J. Inst. Agric. Anim. Sci. 25:55-63 2004